Adult Presentation of Multisystem Inflammatory Syndrome (MIS-A) Post COVID-19 Infection Associated with Myocarditis and Heart Failure: A Case Report - Tarhini, Fadlallah A.; Issawi, Mariam R.; Zorkot, Wael H.; Moulai, Chirine; Taleb, Hussein (International Journal of Innovative Research in Medical Science, 2022)
During the Coronavirus disease 2019 (COVID-19) pandemic, several complications can be noted with different pathophysiology, one of which is multisystem inflammatory syndrome in adults (MIS-A). MIS-A can affect various organ systems, including cardiovascular, gastrointestinal, and neurologic systems without important respiratory involvement. A previously healthy 39-year-old man presented with fever of three days duration accompanied by diaphoresis, conjunctivitis, acute kidney injury, abdominal pain, lethargy, and vomiting. After a comprehensive infectious workup that was unremarkable, his clinical symptoms along with elevated inflammatory markers in the setting of a recent SARS-CoV-2 infection, associated with a trans-thoracic echocardiography revealing biventricular systolic dysfunction, elevated troponin level and normal coronary arteries as evidenced by his angiography, are in favor of myocarditis. Given the constellation of myocarditis, acute kidney injury, conjunctival injection and negative infectious workup, on top of an underlying hyper inflammatory process, the diagnosis of MIS-A was concluded. The patient received supportive treatment with intravenous methylprednisolone. He was started on angiotensin converting enzymes inhibitor (ACE inhibitor) and Beta blocker. He later demonstrated recovery of cardiac function and normalization of inflammatory markers. As the COVID-19 pandemic continues to be a worldwide life-threatening infection, it is important to recognize and diagnose MIS-A, as a potentially fatal clinical syndrome that can lead to severe cardiovascular complications. Further studies and reviews must be focused on more specifications and risk stratifications of this complication, to ensure more feasible and rapid diagnosis, and to avoid its related multi-organ morbidity and mortality.